Cancers Due to Smoking and High Alcohol Consumption: Estimation of the Attributable Cancer Burden in Germany - Mons*, Ute (Dtsch Arztebl Int, 2018)
BACKGROUND: Tobacco and alcohol consumption are known causes of cancer. We set out to estimate the absolute numbers and proportions of cancer attributable to smoking and high alcohol consumption in Germany in 2018. METHODS: Numbers and proportions (population-attributable fractions, PAF) were calculated by sex and age group for ages 35 to 84 years based on population projections, national cancer incidence and exposure data, and published relative risks. RESULTS: For the year 2018 we estimated the smoking-attributable cancer burden to be 85 072 cases (men 58 760, women 26 312), corresponding to 19% of all incident cancers. The highest PAF was seen for lung cancer: 89% of male and 83% of female lung cancer cases are attributable to smoking. The cancer burden attributable to high alcohol consumption was estimated to be 9588 (men 8117, women 1471) cases (2% of all incident cancers). The highest PAF were observed for cancer of the oral cavity and pharynx (men 34%, women 6%) and squamous cell carcinoma of the esophagus (men 30%; women 5%). CONCLUSIONS: A considerable proportion of cancer cases are attributable to smoking and high alcohol consumption. More rigorous prevention efforts are required to achieve significant reductions in the prevalence of these risk factors and the attributable cancer burden.